Fusarium wilt of water melon caused by Fusarium solani in Hungary. - Turóczi, Gy.; Posta, K.; Badenszky, L.; Bán, R. (Plant Breeding and Seed Science, 2011)
Water melon growers in Hungary have been recently reported a disease resembling that of Fusarium wilt developed on Fusarium resistant cultivars. Diseased samples from different regions of Hungary were collected in 2008 and 2009. The pathogen has been successfully isolated and identified as Fusarium solani. All of the isolates are host specific, but are very aggressive on water melon cultivars resistant to F. oxysporum f.sp. niveum. Severe infections occurred only in those fields where water melon has been grown continously for several years, but the pathogen is present in the soil of other fields as well...